Scenarios for the future of the German confectionary market by 2030 - strategic implications for Ferrero Germany: healthy temptation narrative and strategy - Drescher, Janis Nikolai (2023)
This work project explores the future of the German confectionery market employing the ‘Intuitive Logics School’. The report focuses on extensive expert and client involvement, particularly collaborating with Ferrero Deutschland GmbH. The primary objective is to navigate uncertainty, understand plausible events' impacts on industry, retail, and consumers, and respond to an unknown future. The development of plausible scenarios centered on the key uncertainties 'Stability of Supply Chain' and 'Health Regulations' contributes to fostering awareness, as the reader is introduced to one of four potential scenarios. General and scenario-specific strategic implications, offering action plans for the four distinctive futures for Ferrero